Enhancement of sonochemical production of hydroxyl radicals from pulsed cylindrically converging ultrasound waves - Wong, CCY; Raymond, JL; Usadi, LN; Zong, Z; Walton, SC; Sedgwick, AC; Kwan, J (Elsevier, 2023)
Sonochemistry is the use of ultrasound to generate highly reactive radical species through the inertial collapse of a gas/vapour cavity and is a green alternative for hydrogen production, wastewater treatment, and chemical synthesis and modifications. Yet, current sonochemical reactors often are limited by their design, resulting in low efficacy and yields with slow reaction kinetics. Here, we constructed a novel sonochemical reactor design that creates cylindrically converging ultrasound waves to create an intense localised region of high acoustic pressure amplitudes (15 MPaPKPK) capable of spontaneously nucleating cavitation. Using a novel dosimetry technique, we determined the effect of acoustic parameters on the yield of hydroxyl radicals (HO·), HO· production rate, and ultimately the sonochemical efficiency (SE) of our reactor. Our reactor design had a significantly higher HO· production rate and SE compared to other conventional reactors and across literature.